Glial response during cuprizone-induced de- and remyelination in the CNS: lessons learned - Gudi, Viktoria; Gingele, Stefan; Skripuletz, Thomas; Stangel, Martin (Frontiers in Cellular Neuroscience, 2014)
Although astrogliosis and microglia activation are characteristic features of multiple sclerosis (MS) and other central nervous system (CNS) lesions the exact functions of these events are not fully understood. Animal models help to understand the complex interplay between the different cell types of the CNS and uncover general mechanisms of damage and repair of myelin sheaths. The so called cuprizone model is a toxic model of demyelination in the CNS white and grey matter, which lacks an autoimmune component. Cuprizone induces apoptosis of mature oligodendrocytes that leads to a robust demyelination and profound activation of both astrocytes and microglia with regional heterogeneity between different white and grey matter regions. Although not suitable to study autoimmune mediated demyelination, this model is extremely helpful to elucidate basic cellular and molecular mechanisms during de- and particularly remyelination independently of interactions with peripheral immune cells. Phagocytosis and removal of damaged myelin seems to be one of the major roles of microglia in this model and it is well known that removal of myelin debris is a prerequisite of successful remyelination. Furthermore, microglia provide several signals that support remyelination. The role of astrocytes during de- and remyelination is not well defined. Both supportive and destructive functions have been suggested. Using the cuprizone model we could demonstrate that there is an important crosstalk between astrocytes and microglia. In this review we focus on the role of glial reactions and interaction in the cuprizone model. Advantages and limitations of as well as its potential therapeutic relevance for the human disease MS are critically discussed in comparison to other animal models.